Quantifying the Bicycle Share Gender Gap - Kate Hosford; Meghan Winters (Findings, 2019)
In this paper we examine the gender split in 76,981,561 bicycle share trips made from 2014-2018 for three of the largest public bicycle share programs in the U.S.: Bluebikes (Boston), Citi Bike (New York), and Divvy Bikes (Chicago). Overall, women made only one-quarter of all bicycle share trips from 2014-2018. The proportion of trips made by women increased over time for Citi Bike from 22.6% in 2014 to 25.5% in 2018, but hovered steady around 25% for Bluebikes and Divvy Bikes. Across programs, the gender gap was wider for older bicycle share users.